Association Between Mean Platelet Volume to Lymphocyte Ratio (MPVLR) and Diabetic Nephropathy Incidence in Type 2 Diabetes Mellitus - Maisharah; Jelita Siregar; Santi Syafril (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Introduction. Diabetic nephropathy is a microvascular complication of uncontrolled diabetes mellitus (DM), with inflammation among its underlying pathogenesis. Inflammation causes fibrosis, increased vascular permeability, and podocytopathy, which lead to albuminuria. Mean Platelet Volume (MPV) measures thrombocyte size, which may mark increased metabolic and enzymatic activity of thrombocytes. An absolute decrease in lymphocytes occurs due to inflammation-induced decrease in apoptosis. MPVLR value can be used to assess low-grade inflammation in diabetic nephropathy in type 2 DM patients. This study aimed to determine the association between MPVLR values and diabetic nephropathy incidence in type 2 DM. Methods. This study was a cross-sectional study on type 2 DM patients at the Endocrinology outpatient clinic of Adam Malik Hospital aged ≥ 18 years. Sixty patients met the inclusion criteria. Complete blood count, creatinine, and albumin creatinine ratio (ACR) were performed to determine the incidence of diabetic nephropathy. Results. There was a significant difference in age between the diabetic nephropathy and non-nephropathy groups. There were significant differences in absolute lymphocyte count, Hb, HbA1c, and renal parameters such as estimated Glomerular Filtration Rate (eGFR) and creatinine between diabetic nephropathy and non-nephropathy groups. MPVLR showed a significant negative correlation with eGFR and Hb (r = -0.325, p = 0.011), showing that MPVLR increased in line with eGFR and Hb decrease. MPVLR was not significantly associated with diabetic nephropathy incidence based on semiquantitative ACR (p = 0.139). Conclusion. MPVLR was not associated with diabetic nephropathy in type 2 DM patients.